Athlete mental health & psychological impact of sport injury - Haugen, E. (Operative techniques in Sports Medicine, 2022)
Athletes may experience mental health concerns at similar rates, and in some instances, higher rates than non-athletes. Two other factors, sleep and substance use, play important roles in athlete mental health and well-being. A variety of non-sport and sport-related factors place athletes at risk for mental health concerns, and one important sport-related factor is injury. Sport injury and mental health appear to have a bidirectional relationship, and the sport injury and rehabilitation process is associated with a wide variety of psychological and mental health concerns. Existing literature suggests understanding of these variables allows the professional to proactively address psychological readiness for return to sport throughout the injury rehabilitation process. The objective of this paper is to present literature related to athlete mental health and address ways in which sport injury can contribute to athlete mental health, well-being, and psychological readiness for return to sport.